Surgical restorative rehabilitation of an anterior tooth with coronoradicular fracture: case report (Research, Society and Development, 2020)
Introduction: Anterior teeth fractures can cause aesthetic and functional damage. The type, provision and extension of the fracture are determining for prognosis and treatment. Objective: Report the dental management in a patient diagnosed with coronoradicular fracture. Case report: Male patient, 13 years, attended to the Department of Pediatric Dentistry and Orthodontics of FO-UFRJ with trauma report on tooth 21 by falling from his own height at school about 3 months ago. Clinically, it was noted a mesial fracture line and, through radiographic examination, it was noted the fracture in the cervical third of the root, adjacent to the pulp wall. The affected tooth showed a positive response to the vitality test, negative on palpation/percussion pain and no periodontal alteration. The treatment plan consisted in the periodontal flap surgery without relief and subsequent fragment bonding. Conclusion: The post-trauma care should be immediate to enable effective treatment without sequel. In this report case, the clinical follow-up by an interdisciplinary team provided a conservative and aesthetic therapeutic decision through the fragment bonding technique.